Quantifying river losses on the Sundays River between Darlington Dam and Korhaans Drift Weir through hydrodynamic modelling - Nel, Aldré (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng) -- Stellenbosch University, 2022.